MlNERALOGICAL STUDY OF BISMUTH - GOLD - ANTIMONY MINERALIZATION AT THE AREA OF KAMARIZA, LAVRION - Σολωμός, Χ.; Βουδούρης, Π.; Κατερινόπουλος, Α. (Bulletin of the Geological Society of Greece, 2004)
At the Lavrion mine, area, near the village of Kamariza, an oxidized mineralization unusually rich in bismuth, gold, antimony and copper has been studied. Three different parageneses have been recognized and described: a) a copper-rich assemblage, containing chalcopyrite, chalcocine, digenite, covelline, azurite, malachite and georgeite, b) a bismuth-gold-rich assemblage, consisting of native bismuth, bismuthinite, native gold, bismite, bismutite, beyerite, kettnerite, preisingerite, rooseveltite and mixité and c) an antimony-rich one, comprising stibiconite, bindheimite, mimetite and gartrellite. The mineral study suggests that the primary mineralization should consist of pyrite ± arsenopyrite, chalcopyrite, bismuthinite (and/or bismuth sulphosalts), native bismuth, maldonite (which has been exsoluted to gold and bismuth) and bournonite. The oxidation of this primary mineralization and the reac ion with supergene solutions containing significant amounts of HCO3" and HAsCV2 - H2ASO4", caused the formation of 17 secondary minerals.